Exercise and Inflammation in Pediatric Crohn’s Disease - Ploeger, H.; Obeid, J.; Nguyen, T.; Takken, T.; Issenman, R.; de Greef, M.; Timmons, B. (International Journal of Sports Medicine, 2012)
We examined inflammatory cells, cytokines and growth factors in response to acute bouts of moderate intensity continuous exercise and high intensity intermittent exercise in youth with Crohn’s disease and in healthy matched-controls. 15 patients and 15 controls performed 30 min of cycling at 50% of peak mechanical power (PMP) and 6 bouts of 4×15-s of cycling at 100% PMP. Blood was collected at rest, at the mid-point, at the end of exercise and at 30 and 60 min into recovery. In patients with CD, both types of exercise increased immune cells and GH and decreased IGF-I. Moderate intensity exercise induced a greater increase in leukocytes (p<0.05), neutrophils (p<0.05), lymphocytes (p<0.001), monocytes (p<0.05), IL-6 (p<0.05), IL-17 (p<0.05) and GH (p<0.05) and a similar decrease in IGF-I, compared with high intensity exercise. TNF-α did not change significantly with either exercise. Responses in patients were similar compared with controls; however, in patients monocytes remained elevated significantly longer in response to MICE. Youth with Crohn’s disease can engage in distinctly different types of exercise without a significant acute exacerbation of inflammation.
Keywords: children; cycle ergometry; cytokines; growth factors; inflammatory bowel disease